Pengaruh Sanksi Perpajakan, Tingkat Pendapatan, Dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Dengan Kesadaran Wajib Pajak Sebagai Variabel Intervening (Jurnal Kendali Akuntansi, 2024)
This research aims to determine and test the influence of tax sanctions, income level and tax socialization on taxpayer compliance with taxpayer awareness as an intervening variable. In this research, researchers examine the compliance of taxpayers who have a NPWP and are registered with KPP Pratama Gresik. The population of this research is individual taxpayers who have income in the Gresik Regency area. Sampling used purposive sampling with a sample size of 97 respondents. This research uses primary data in the form of questionnaire answers distributed to taxpayers. This research method is quantitative using SmartPLS as a testing tool. The results of the direct influence test show that tax sanctions and tax socialization have no effect on taxpayer compliance, while income level and taxpayer awareness have a significant positive effect on taxpayer compliance. Tax sanctions and income level have a significant positive effect on taxpayer awareness, while tax socialization has no effect on taxpayer awareness. The results of indirect hypothesis testing show that taxpayer awareness is able to mediate the effect of tax sanctions and income level on taxpayer compliance. Meanwhile, taxpayer awareness is unable to mediate the influence of tax socialization on taxpayer compliance.